Development and social policy reform in Uganda: The slow emergence of a social protection agenda (1986-2014) - Grebe, Eduard; Mubiru, John Bosco (Centre for Social Science Research University of Cape Town, 2014)
This paper provides a broad overview of the evolution of development and welfare policy—and the politics surrounding—it in Uganda, but focuses primarily on the increasing prominence of social protection, especially cash transfers, on the domestic political agenda. It analyses both how and why the development and social policy agendas almost fully excluded social protection prior to 2002, but then increasingly embraced it, especially since 2006. Non-contributory social assistance in the form of cash transfers have not traditionally played a significant role in Ugandan development and poverty reduction policy, with policymakers tending to focus on economic growth as a source of prosperity (expected to extend to all sections of society), with opponents seeing cash transfers (and social assistance more broadly) as unaffordable and counter-productive ‘hand-outs’ that create dependence on the state and disincentivise productive work. From the early 2000s donors, sections of the bureaucracy and civil society promoted cash transfers with limited success. But after 2006, systematic promotion of cash transfers started to bear fruit, and from 2010 a largely donor-funded cash transfer pilot scheme known as the Social Assistance Grants for Empowerment (SAGE) programme has been implemented in fourteen districts (with a fifteenth added in 2013). The paper describes the evolution of Ugandan development policy and highlight the political factors that have in the past been obstacles to social protection programmes featuring prominently on the development agenda (including the predominant socio-economic development paradigm, negative elite attitudes, resistance from conservative technocrats and lack of familiarity among key decision-makers) and examine how these have increasingly been overcome by the proponents of social protection. While donors have played a critical role in the promotion of social protection and cash transfers, other actors—including civil society and social development bureaucrats—and macropolitical factors (including electoral competition, changing international development discourse, emerging evidence from other countries, etc.), have also contributed to increased domestic political support. We conclude that the very existence of SAGE and the politics surrounding the pilot indicate a significant change in attitudes among a large proportion of policy-makers, including some historically sceptical technocrats, and political leaders, but that resistance is likely to continue from certain quarters and that the future of cash transfers remains uncertain.